PTU-026 Prevalence of liver histological abnormalities in type 1 diabetes and the long term consequences. (28th May 2012) - Harman, D J; Harris, R; Gazis, A; Kaye, P; Aithal, G
Abstract : Introduction: Patients with type 1 diabetes have a higher prevalence of raised liver enzymes than the general population. Ultrasound diagnosis of non-alcoholic fatty liver disease has been reported to be common in type 1 diabetes despite associated insulin deficiency rather than insulin resistance. However, the histological spectrum of liver disease in type 1 diabetes and the natural history of chronic liver disease in this cohort is unknown. We describe the histological findings of patients with type 1 diabetes who had liver biopsy in a tertiary referral centre, and their long-term clinical outcome. Methods: The DIAMOND database, which contains longitudinal data for over 95% of type 1 diabetes patients from an overall catchment population of 750 000 in Nottingham, was crossmatched with the clinical pathology database to identify those who had undergone liver biopsy. Case notes were reviewed to obtain follow-up data, and identify liver and non-liver related outcomes. Results: Out of 2800 patients with Type 1 Diabetes, 57 patients underwent a total of 82 liver biopsies. Common indications for biopsy were abnormal liver enzymes (28 patients), malignancy (8), Hepatitis C staging (7) and clinical evidence of cirrhosis (3). On index biopsy, 86% had significant histological abnormalities (Abstract PTU-026 figure 1 ) and 10 patients (17.5%) had cirrhosis. During a total follow-up of 336.4 patient years (median 5.6 years), a further four patients developed cirrhosis, giving a cirrhosis prevalence of at least 500 per 100 000 population—this compares with an estimated UK cirrhosis prevalence of 76.3 per 100 000 population. 1 Portal hypertensive sequelae occurred in 11 patients (78.6%) with cirrhosis and hepatocellular carcinoma in three patients. 22 patients (38.6%) died during follow-up. Crude death rate was 6539 per 100 000 person years, compared with national Type 1 Diabetes data 2 of 1878 per 100 000 person years. Conclusion: Type 1 Diabetes is associated with significant liver histology abnormalities and a higher than expected occurrence of cirrhosis, portal hypertension and mortality. These findings have implications for long-term management of patients with Type 1 Diabetes. Competing interests: None declared. References: 1. Fleming KM, Aithal GP, Solaymani-Dodaran M, et al. Incidence and prevalence of cirrhosis in the United Kingdom, 1992-2001: a general population-based study. J Hepatol 2008;49 :732–8. 2. NHS IC . National Diabetes Audit Mortality Analysis 2007-2008 . NHS IC, 2011.